The Relationship Between Self-Control and Consumptive Behavior Among Students Living in Dormitories - Kristiani Marbun; Doli Maulana Gama Samudera Lubis (Psikologi Prima, 2026)
The rapid development of digital technology and e-commerce has increased the ease of online shopping activities, but it has also contributed to the rise of consumptive behavior, particularly among university students with high levels of technology use. This study aimed to examine the relationship between self-control and online shopping consumptive behavior among female students living in the dormitory of Universitas Medan Area. The study employed a quantitative approach with a correlational research design. The population consisted of dormitory students, with a sample of 67 students selected using purposive sampling techniques. Data were collected using psychological scales, namely a self-control scale and an online shopping consumptive behavior scale, both constructed using a Likert scale format. Data analysis was conducted using the Pearson Product Moment correlation technique. The results revealed a significant negative relationship between self-control and online shopping consumptive behavior (r = -0.54; p < 0.05). These findings indicate that higher levels of self-control are associated with lower tendencies toward consumptive online shopping behavior. Conversely, students with lower self-control are more likely to engage in consumptive behavior in the digital era.